Mockito tutorial : learn mocking with 25 JUnit examples - Karanam, Ranga (Packt Publishing, 2018)
"Writing great unit tests distinguishes good programmers from great programmers. In this course, you will learn how to write great unit tests with Mockito and JUnit. You take 12 steps with JUnit and 18 steps with Mockito into unit testing proficiency."--Resource description page